OBSERVATIONS ON HUMMINGBIRDS AND THEIR NECTAR RESOURCES AT THE CLOUD FOREST OF MANU ROAD, PERU - González, Oscar (2020)
We studied hummingbird ecology in the cloud forest of southeastern Peru, using mist nets and direct observations. This study was done in one area of the cloud forest of Manu road (Cuzco, Peru) at the beginning of the rainy season of 2011. We give a list of the hummingbirds (14 species) and the flowering plants that they use as nectar resources (~20 taxa in 11 families). We also comment on the abundance, distribution and importance of the hummingbird's role in the cloud forest ecosystem.